2016
DOI: 10.1093/rheumatology/kew015
|View full text |Cite
|
Sign up to set email alerts
|

Synovitis, acne, pustulosis, hyperostosis and osteitis syndrome: a single centre study of a cohort of 164 patients

Abstract: SAPHO syndrome is predominant in middle-age women, characterized by dermatological and osteoarticular manifestations with unknown aetiology. CT scan and bone scintigraphy are useful for diagnosis. There is still no standard treatment to control the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
81
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 26 publications
8
81
0
2
Order By: Relevance
“…However, 1.2% of the patients were RF positive in our SAPHO cohort with 164 patients. [1] In another study, anti-CCP antibody was negative in all the 69 patients tested. [14,15] Only 1 similar case who concurrently fulfilled the diagnostic criteria for both RA and SAPHO syndrome was previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, 1.2% of the patients were RF positive in our SAPHO cohort with 164 patients. [1] In another study, anti-CCP antibody was negative in all the 69 patients tested. [14,15] Only 1 similar case who concurrently fulfilled the diagnostic criteria for both RA and SAPHO syndrome was previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The osteoarthritic disorders mainly affect the anterior chest wall (ACW, including sternoclavicular, manubriosternal, and costosternal joints), the spine and sacroiliac joint. [2] However, the appendicular skeleton, especially the small joint is a less frequently affected site in SAPHO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research team previously reported the largest cohort study of SAPHO syndrome in the world, including one hundred and sixty-four patients [21]. In this study, psychiatric evaluation and MRI scans were performed on twenty-eight patients of these SAPHO patients, and fourteen SAPHO patients were diagnosed with depression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to identify depression in SAPHO patients as it may have similar effect on AS/psoriatic patients. Our research team is involved in the largest cohort study of SAPHO syndrome in the world [21]. When assessing the clinical, laboratory and radiological features of SAPHO syndrome, we also tried to explore the episode of depressive symptoms in SAPHO patients and revealed neurobiological basis of depression symptoms in these patients using rs-fMRI.…”
Section: Introductionmentioning
confidence: 99%